Analisis pendapatan pengusaha industri rumah tangga batik di Kota Jambi - Fitri, Nuril; Tan, Syamsurijal; Umiyati, Etik (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
The purposes of this study are 1) Knowing and analyzing the socio-economic conditions of the batik home industry entrepreneurs in Jambi City. 2) Knowing and analyzing the factors that affect the income of batik home industry entrepreneurs in Jambi City. 3) Knowing the strategies for increasing the income of batik home industry entrepreneurs in Jambi City. Analysis tools used are multiple linear regression and SWOT analysis. Based on the results of multiple linear regression, it can be concluded that partially fixed capital, operational capital, labor, length of business, price, and sales volume have a significant effect on the income of batik entrepreneurs, while fixed capital and labor variables have no significant effect on batik entrepreneurs in Indonesia. Jambi City. The results of the SWOT matrix, it is divided into S-O strategy, W-O strategy, S-T strategy, and W-T strategy, and based on the results of the EFAS calculation the probability of O (8.00) > T (7.00). So it is clear that the batik industry in Jambi City is in a good position, namely aggressive/developing (SO strategy).